2017
DOI: 10.4103/1735-9066.205966
|View full text |Cite
|
Sign up to set email alerts
|

How to prevent workplace incivility?: Nurses' perspective

Abstract: Background:Many articles have studied workplace incivility and its influence on outcomes, but very few have been conducted to assess how to prevent this issue. In this study, we aimed to determine how to prevent workplace incivility from the nurses' perspective.Materials and Methods:This was a qualitative study which was based on a conventional content analysis approach. Thirty four nurses (25 to 52 years old) from seven training hospitals in Tabriz, Iran were selected through purposive sampling. Thirty six se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 39 publications
(46 reference statements)
2
13
0
Order By: Relevance
“…Workplace incivility has been documented internationally as significantly prevalent in the workplaces of nurses. For example, in one study in Iran, high incivility prevalence was reported amongst 34 Iranian nurses from seven hospitals (Abdollahzadeh et al, 2017). In one study in China, WPI increased anxiety and burnout level, as reported by 696 new nurses .…”
Section: Background Of the Studymentioning
confidence: 97%
See 4 more Smart Citations
“…Workplace incivility has been documented internationally as significantly prevalent in the workplaces of nurses. For example, in one study in Iran, high incivility prevalence was reported amongst 34 Iranian nurses from seven hospitals (Abdollahzadeh et al, 2017). In one study in China, WPI increased anxiety and burnout level, as reported by 696 new nurses .…”
Section: Background Of the Studymentioning
confidence: 97%
“…Workplace incivility is troubling not only to the healthcare provider but also to the delivery of care beneath the shade of incivility (Abdollahzadeh et al, 2017). Pearson, Andersson, and Wegner (2001) stated that "WPI is low-intensity divergent behaviour with uncertain intention to injure a person, violating the workplace standards and norms for reciprocal respect."…”
Section: Background Of the Studymentioning
confidence: 99%
See 3 more Smart Citations